Working with communities and building local institutions for sustainable land management in the Ethiopian highlands - Amede, Tilahun; Kassa, H.; Zeleke, G.; Shiferaw, A.; Kismu, S.; Teshome, M. (International Mountain Society (IMS) and United Nations University, 2007)
Land management is a multi-dimensional and multi-institutional engagement that demands collective analysis, design, and implementation of innovations. Its importance for Ethiopia cannot be overemphasized, as land degradation threatens food security and environmental sustainability. Building on a specific case study of a project in Southern Ethiopia, the present article describes how the government and non-state agencies are collaborating to learn together while promoting improved land management practices and implementing land rehabilitation programs in communal areas and farmlands in the Ethiopian highlands. Ensuring full involvement and commitment of stakeholders at different levels, building the capacity of local institutions, and redefining the role of communities and the state in a dynamic way are essential prerequisites for success. Suggestions have also been formulated to facilitate wider adoption and scaling up of improved land management innovations.